Motivation factors on knowledge sharing in public sector organizations / Mohd Adib Suhaimi - Suhaimi, Mohd Adib; Sepe, Mohamad Anuar (2015)
A study has been conducted to explore the motivation factors on knowledge sharing among public sector organizations in Malaysia. Nowadays, knowledge management has been identified by most of the organizations as a positive force in creating new knowledge hence increase sustainable competitive advantage. Many researchers have agreed on the importance of knowledge management as the process that should integrate individual talents, culture and technology to increase the knowledge generated throughout the organizations. Knowledge sharing is the most essential part in the implementation of knowledge management. Application of knowledge sharing culture in both public and private sector organizations may develop efficiency and effectiveness of service delivery. Malaysia’s public sectors have promoted numbers of key measures to enhance economy-wide productivity, accelerate economic growth as well as to develop innovation and creativity towards better quality, responsive and knowledge-based public services. Thus, this paper proposes a conceptual model which identifies the motivation factors that promote knowledge sharing in the public sector organizations. The findings provided some empirical support for the conceptual framework. It is assumed that there is a significant relationship between variables includes individual attitude, social interaction, organization culture, supportive leader as well as technology application and knowledge sharing. By educate the employees with the appropriate knowledge sharing in their mindset and technology to support them will rapidly bring a knowledge sharing culture in the public sector organizations in increasing the capability of service delivery.